Lower Self-Reported Quality of Life in HIV-Infected Patients on cART and With Low Comorbidity Compared With Healthy Controls. (1st September 2015) - Pedersen, Karin K.; Eiersted, Morten R.; Gaardbo, Julie C.; Pedersen, Maria; Gerstoft, Jan; Troseid, Marius; Nielsen, Susanne D.
Abstract : Background: Self-reported quality of life (QoL) has previously been found to be impaired in patients living with HIV and associated with viral replication, degree of immunodeficiency, and comorbidity. We aimed at investigating QoL in a group of HIV-infected patients with suppressed viral replication and with low comorbidity, compared with healthy controls. We furthermore aimed to identify factors associated with QoL. Design and Methods: Cross-sectional study of 52 HIV-infected patients and 23 healthy controls matched on age, gender, education, and comorbidity. HIV-infected patients and healthy controls had previously been examined regarding cognitive, physical, metabolic, and immunological parameters. QoL was investigated using the Medical Outcomes Study HIV Health Survey (MOS-HIV). Linear multiple regression models were created to find factors associated with mental health summary score (MHS) and physical health summary score (PHS). Results: HIV-infected patients reported lower QoL compared with controls. In HIV-infected patients, female gender and depression score were associated with lower MHS. In controls, years of education, depression score, and cognitive test performance were associated with lower MHS. In HIV-infected patients, years of education, depression score, and body mass index were associated with lower PHS, whereas in controls, years of education and fitness level were associated with PHS. Conclusions: Even well-treated HIV-infected patients with low level of comorbidity reported lower QoL compared with healthy controls. Especially, depression score and body mass index were associated with QoL in HIV-infected patients.